Creative teaching and its assessment - Palaniappan, Ananda Kumar (2009)
In recent years, there has been much emphasis and motivation for teaching both at the secondary school and tertiary level to move from the traditional „chalk and talk‟ to a more creative and innovative teaching methodology. The Malaysian Education Ministry has initiated many training programs as well as curricular and evaluation changes to initiate this change which also included critical thinking. Various policies have been formulated together with huge investments on infrastructure and funding to accelerate this change. Hence, it is imperative to evaluate to what extent creative teaching has actually being carried out. In order to do this, it is vital to have a valid and reliable measure of creative teaching. This paper aims to first present the various components of creative teaching as theorized and reported in literature. Based on significant findings and factors gleaned from these reviews a creative teaching inventory was designed This instrument was tested for its reliability and validity. Secondly, this paper aims to discuss the issues and factors influencing the implementation of creative teaching in the classroom. Among them are the issues relating to creative teaching and learning which involve not only the pedagogical aspect but also the content and the learning processes. Teacher and student variables, such as attitude and perception were also found to be significant in determining the efficacy of creative teaching. The findings from internal reliability tests based on data from secondary school teachers indicate that this inventory is a stable measure of creative teaching. Factor analyses provide the empirical support for the validity of this instrument. However, it is suggested that further investigations using teachers at other levels of education may throw more light on the validity and reliability of this instrument and the findings. Pedagogical, curricular and policy implications based on the findings are also discussed.